Bisoprolol effectiveness in arterial hypertension and coronary heart disease - O. D. Ostroumova; M. L. Maksimov; A. M. Rykova (Кардиоваскулярная терапия и профилактика)
The authors review the current evidence on the effectiveness of a highly selective b-adrenoblocker bisoprolol in the treatment of arterial hypertension and/or coronary heart disease. The issues of bisoprolol therapy in the specific clinical subgroups of cardiac patients (such as elderly people and smokers) are discussed.